Thermal treatment of petroleum-contaminated marine sediment according to oxygen availability and temperature: Product quality as a potential plant-growth medium - Kim, Kibeum; Kwon, Hyun-ah; Park, Jaebeom; Lee, Hyeonmin; Choi, Yongju (Chemosphere (Oxford), 2023)
The sustainable management of dredged sediment from contaminated sites needs to consider the end-use of the treated sediment. In this regard, modifying conventional sediment treatment techniques to generate a product that is suitable for a range of terrestrial uses is necessary. In the present study, we evaluated the product quality of treated sediment as a potential plant-growth medium following the thermal treatment of marine sediment contaminated by petroleum. The contaminated sediment was subject to thermal treatment at temperatures of 300, 400, or 500 °C, and no, low, or moderate oxygen availability, and the resulting treated sediment was analyzed in terms of its bulk properties, spectroscopic properties, organic contaminants, water-soluble salts and organic matter, and the leachability and extractability of heavy metals. All operational combinations for the treatment process reduced the total petroleum hydrocarbon content of the sediment from 4922 mg kg−1 to lower than 50 mg kg−1. The thermal treatment process stabilized the heavy metals in the sediment, reducing the zinc and copper concentration by up to 58.9% and 89.6%, respectively, in the leachate from the toxicity characteristic leaching procedure. The hydrophilic organic and/or sulfate salt byproducts of the treatment were phytotoxic, but these can easily be removed by washing the sediment with water. By combining the sediment analysis results with experimental data from barley germination and early-growth tests, the end product was found to be of higher quality when higher temperatures and lower oxygen availability were employed in the treatment process. These findings demonstrate that it is possible to retain the natural organic resources of the original sediment by optimizing the thermal treatment, thus ensuring a suitably high product quality for use as a plant-growth medium. [Display omitted] •Quality of thermally treated marine sediment was comprehensively evaluated.•Oxygen availability and temperature strongly affect the treated sediment quality.•Thermal treatment stabilizes metals while producing water-soluble toxicants.•Water-washing post-treatment enables producing high-quality media for plant growth.•For product quality pyrolytic conditions are superior to oxidative conditions.